Developing an Innovation Management Strategy for Educating Managers on Disaster risk reduction - V. A. Puchkov (Управленческие науки)
In modern conditions of increasing threats, challenges, dangers and threats of various types, it is necessary to create a system of innovative training of managers. The paper considers the formation of an innovation management strategy for education of managers on disaster risk reduction and the development of methodological support for this activity. In the course of work to achieve the goal, key tasks were solved: the organizational basis for the formation of an integrated education system was justified, proposals for creating an information and organizational learning innovation were developed, and the basis for a new unified innovative information and communication educational platform was created. Methodological recommendations for innovative training of managers are proposed. The research methodology provides for the creation of innovative and technological matrixes of Executive education based on modern methods of analysis and synthesis, expert assessments, modeling, analogies, and observation. The results of the research are the main provisions of the innovation management strategy for education of managers on disaster risk reduction, organizational and methodological support for this activity. On their basis, a comprehensive system of training managers has been created, and modern training programs and practices in the field of disaster management have been introduced. Recommendations for the consolidation of key modern achievements of science and technology in the educational sphere are formulated. The study may be of interest to state authorities in the formation and implementation of the state strategy of innovative management of education of managers, which provides a high modern level of training.